2003
DOI: 10.1902/jop.2003.74.6.849
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐Rich Plasma Contains High Levels of Platelet‐Derived Growth Factor and Transforming Growth Factor‐β and Modulates the Proliferation of Periodontally Related Cells In Vitro

Abstract: These data demonstrated that both PDGF-AB and TGF-beta1 were highly concentrated in the PRP preparations. It is suggested PRP modulates cell proliferation in a cell type-specific manner similar to what has been observed with TGF-beta1. Since synchronized behavior of related cell types is thought to be required for successful periodontal regeneration, it is further suggested these cell type-specific actions may be beneficial for periodontal regenerative therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
287
0
16

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 340 publications
(327 citation statements)
references
References 33 publications
13
287
0
16
Order By: Relevance
“…Platelet rich fibrin (PRF) is a recent but promising advancement in the field of regenerative therapy. High concentrations of tissue growth factor β and platelet derived growth factor present in PRF have angiogenic, proliferative and differentiating effects on osteoblasts (Okuda et al, 2003). PRF has been successfully used with different graft materials in the treatment of infrabony defects (Dori et al, 2007;Piemontese et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Platelet rich fibrin (PRF) is a recent but promising advancement in the field of regenerative therapy. High concentrations of tissue growth factor β and platelet derived growth factor present in PRF have angiogenic, proliferative and differentiating effects on osteoblasts (Okuda et al, 2003). PRF has been successfully used with different graft materials in the treatment of infrabony defects (Dori et al, 2007;Piemontese et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated that the use of platelet rich fibrin helps is the better and faster healing of the operative site [11][12][13]. Platelet rich fibrin acts as a source of growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that TGF-β 1 stimulates the proliferation and differentiation of osteoblasts and induces bone formation 27,28) , however, its effects on bone healing appear inconsistent. Regarding the soft tissue healing, Okuda et al 29) demonstrated that this growth factor stimulated the biosynthesis of extracellular matrix components such as type I collagen, proteoglycan, glycosaminoglycan, and fibronectin. TGF-β 1 also appears to inhibit the formation of extracellular matrix degrading protease and as a result it enhances the formation of granulation tissue.…”
Section: ⅳ Discussionmentioning
confidence: 99%